The shackles of power : three Jeffersonian decades - Dos Passos, John, 1896-1970 (Garden City, New York : Doubleday & Company, Inc., 1966)
An historical narrative of the early United States as dominated and influenced by Jefferson, Monroe, Madison, and John Quincy Adams. Pictures the first quarter of the 19th century as abounding in both patriots and scoundrels-enough to make for fascinating reading.
A reception at the president's house -- The arch traitor Burr -- The labor and contentions of public life -- Confrontation at Richmond -- All the odious passions -- From the groves of Monticello -- The sevenfold wonders of the time -- The easy work of peace -- The more general diffusion of knowledge -- Of democracy in America.
"Reading on the Jeffersonian era": pages 409-412.
Also issued online.
Keywords: Jefferson, Thomas, -- 1743-1826.; 1783-1865; Histology; UNITED STATES -- HISTORY; ADAMS, JOHN QUINCY, 1767 -- 1848.; MADISON, JAMES, 1751 -- 1836.; MONROE, JAMES, 1758.; United States -- History -- 1783-1865.